The advance of Fusarium wilt tropical race 4 in Musaceae of Latin America and the Caribbean: Current situation - Martínez, Gustavo (2023)
The fungus Fusarium oxysporum f. sp. cubense tropical race 4 (syn. Fusarium odoratissimum) (Foc TR4) causes vascular wilt in Musaceae plants and is considered the most lethal for these crops. In Latin America and the Caribbean (LAC), it was reported for the first time in Colombia (2019), later in Peru (2021), and recently declared in Venezuela (2023). This work aimed to analyze the evolution of Foc TR4 in Musaceae in LAC between 2018 and 2022. This perspective contains a selection of topics related to Foc TR4 in LAC that address and describe (i) the threat of Foc TR4 in LAC, (ii) a bibliometric analysis of the scientific production of Foc TR4 in LAC, (iii) the current situation of Foc TR4 in Colombia, Peru, and Venezuela, (iv) medium-term prospects in LAC member countries, and (v) export trade and local food security. In this study, the presence of Foc TR4 in Venezuela and the possible consequences of the production of Musaceae in the long term were reported for the first time. In conclusion, TR4 is a major threat to banana production in Latin America and the world, and it is important to take measures to control the spread of the fungus and minimize its impact on the banana industry. It is important to keep working on the control of Foc TR4, which requires the participation of the local and international industry, researchers, and consumers, among others, to prevent the disappearance of bananas.